A=-10 all you do to find a is simply add 2 to both sides of the equal sign
The function y = 1100.74x - 1976.47 represent the total number of visitors x years after 2005.
<h3>What is an
equation?</h3>
An equation is an expression that shows the relationship between two or more variables and numbers.
Let y represent the total number of visitors x years after 2005. Hence:
y = 1100.74x - 1976.47
The function y = 1100.74x - 1976.47 represent the total number of visitors x years after 2005.
Find out more on equation at: brainly.com/question/13763238
#SPJ1
9514 1404 393
Answer:
2.83 for log2(x)
15.81 for log(2x)
Step-by-step explanation:
We can get the log function by itself by subtracting the constant and dividing by the coefficient.
5 +6·log2x = 14
6·log2x = 9 . . . . . . . subtract 5
log2x = 1.5 . . . . . . . divide by 6
At this point, we're not sure what is meant by log2x.
log₂(x) = 1.5 ⇒ x = 2^1.5 ≈ 2.83
log(2x) = 1.5 ⇒ x = (10^1.5)/2 ≈ 15.81
Answer:
-11
Step-by-step explanation:
If we call x the least integer, then x + 1 is the next integer, and x + 2 is the greatest integer.
x (x + 1) (x + 2) = -1716
x (x² + 3x + 2) = -1716
x³ + 3x² + 2x = -1716
x³ + 3x² + 2x + 1716 = 0
That's not an easy equation to factor. We could use rational root test, but that would take a long time. However, we can narrow down the options logically. The three integers are relatively close together, so if we approximated the product as x³:
x³ ≈ -1716
x ≈ -11.9
So let's see if x = -12 is a solution:
(-12)³ + 3(-12)² + 2(-12) + 1716 = 396
Nope. Let's try x = -11:
(-11)³ + 3(-11)² + 2(-11) + 1716 = 726
Not that either. Let's go the other direction, x = -13:
(-13)³ + 3(-13)² + 2(-13) + 1716 = 0
Aha! x = -13. So x + 1 = -12, and x + 2 = -11.
-11 × -12 × -13 = -1716
The greatest integer is -11.
Answer:
12x² - 4x - 8
Step-by-step explanation:
Use FOIL method
(3x + 2)(4x - 4) = 3x*4x + 3x*(-4) + 2 *4x + 2*(-4)
= 12x² - 12x + 8x - 8 {add like terms}
= 12x² - 4x - 8
Hint: 3x * 4x -----> Multiply the coefficients = 3 *4 = 12 and then multiply the variables and for multiplying the two variable, add the powers
x*x =![x^{1+1)=x^{2}](https://tex.z-dn.net/?f=x%5E%7B1%2B1%29%3Dx%5E%7B2%7D)
3x * 4x = 12x²